FRP interlocking multi-spiral reinforced square concrete columns: A promising compression application for marine engineering. (1st October 2021) - Fang, Shu; Li, Lijuan; Lin, Lianghao; Wang, Hongliang; Fang, Zhuangcheng; Li, Zewei; Xiong, Zhe; Liu, Feng
Highlights: Pioneer study on FRP interlocking multi-spiral reinforced SWSSC square columns. Axial compressive behaviors of FRP-IMS-RSWSSCs are investigated. FRP-IMS-RSWSSCs show attractive compressive deformability. Interactions between FRP interlocking multi-spirals are revealed. The axial load-strain model is proposed based on section analyses. Abstract: The hybrid utilization of seawater sea-sand concrete (SWSSC) and fiber-reinforced polymer (FRP) composites to create innovative structures show promising application prospects in marine infrastructure construction, as it achieves steel corrosion elimination and use of available local materials. A potential combination of SWSSC and FRP is FRP-reinforced SWSSC columns. The rectangular or square stirrups provide inefficient confinement to the in-filled concrete compared to circular spirals, which limits practical applications of FRP-reinforced SWSSC square columns. The interlocking multi-spiral configuration may be a viable option, including a large circular spiral interlocking with four small spirals at column corners. In this study, the axial compressive performance of square SWSSC columns reinforced with glass FRP interlocking multi-spirals is investigated. Main variables are FRP transverse reinforcement configurations, spacings, and corner spiral sizes of interlocking multi-spirals. Test results confirmed that corner spirals provided additional confinement to the central spiral and longitudinal reinforcement, and decreases in spacings and corner spiral sizes effectively improved the post-peak compressive behavior. Moreover, comparisons between FRP transverse reinforcements indicated that interlocking multi-spirals enabled columns to exhibit better deformability than stirrups with identical amounts. A modified theoretical model was developed based on section analyses, which provided reasonably accurate predictions of test results.